LOCAL CULTURE-BASED ENTREUPREUNERSHIP EDUCATION IN THE BLURU VILLAGE COMMUNITY IN SIDOARJO DISTRICT, SIDOARJO DISTRICT - Niswatin,; Wasino,; Suyahmo,; Arsal, Thriwaty (International Journal of Psychosocial Rehabilitation, 2020)
Entrepreneurship today is one of the pillars of the people's economy. The era of globalization makes our country part of the ASEAN Economic Community (MEA) so that it demands the community to continue to innovate to explore the potential of the creative economy. This study aims to analyze the importance of local culture as a potential asset to develop entrepreneurship education among the people of Bluru Village, Sidoarjo District, Sidoarjo Regency. This research uses a qualitative approach. Data collection techniques using observation, interviews, and study literature. Analysis of the data used is descriptive qualitative. The results of this study indicate the existence of entrepreneurship education in the Bluru Village community at the time of the people's party, namely; looking for opportunities and initiatives, taking risks, perseverance, persuasion and networking, independence and confidence.